Recovery of chromate from chrome electroplating waste water by anion exchange resin method - Vu Kiem Thuy. (March 2009)
This research investigates the recovery of Cr(VI) from Chrome electroplating waste water using anion exchange method. The experiment was carried out using four types of anion resins including 2 types of weak base anion resins and 2 types of strong base anion resins from different manufacturers. Their iso-kinetics and ion exchange equilibria were determined by batch method with Chromate prepared solution and actual wastewater to determine which type of anion resin has the best ability for Chromate removal. Based on the results of the batch method, the best chromate absorbent resins were chosen for column experiment with actual electroplating wastewater. The best resins were strong base anion resins, especially Purolite A 400. It is better than the other resins based on chromate removing efficiency and chromate recovery. Another resin that used for column experiment was Lewatit Monoplus M500 (strong base anion resing). Both resins gave above 99% removal efficiency and more than 60% chromate recovery based on the column test. The result of the study showed that M500 and A400 has the potential for the removal and recovery of chromate from electroplating waste water.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman.
Keywords: Chromium compounds